Integrating Discovery Learning and PjBL in EFL: Teaching Materials, Tasks, and Assessment - Nisa, Asri Ainun; Safitri, Ayu; Halla, Maulana Ahsan; nugraha, irsyad (Ma'soem University, 2025)
The combination of Discovery Learning and Project-Based Learning (PjBL) in English as Foreign Language (EFL) classrooms is acknowledged as an effective strategy to boost student engagement and language development. This research fills a gap by examining the integrated application of Discovery Learning and PjBL in an Indonesian public school context, specifically in class XI 5 at SMAN 11 Garut. It focuses on how teaching materials, project assignments, and assessment methods are designed and implemented. Employing a qualitative case study method, the data were gathered through classroom observations, a review of instructional resources, and analysis of students’ project results, particularly their video-based conversation tasks. The results reveal that materials grounded in Discovery Learning assist in organizing the learning process, while project tasks enable students to express creativity and practice communication skills, as shown in their video projects. Furthermore, formative assessments offer meaningful feedback on student progress and learning difficulties. Despite challenges such as student preparedness and technical issues in video creation, the integration of these approaches shows strong potential in creating an engaging and purposeful EFL learning environment. The study offers practical recommendations for EFL educators in designing instructional content and assessment aligned with Discovery Learning and PjBL, and also discusses the implications for future curriculum and project-based teaching practices.